Distribution and association pattern of pasak bumi (Eurycoma longifolia) in Batang Lubu Sutam District, Padang Lawas, North Sumatra. Issue 1 (November 2021) - Susilowati, A; Rachmat, H H; Yulita, K S; Elfiati, D; Ginting, I M
Abstract: Pasak bumi ( Eurycoma longifolia ) is a medicinal plant with various benefits and has long been used to cure various diseases such as cancer, gingivitis, intestinal worms, and anti-inflammatory anti-malarial, and tonic after childbirth. The root has high economic value leading to unsustainable harvest and drastic population decline. As initial data in conservation activities, information regarding the association of pasak bumi in Batang Lubu Sutam natural forest has not been obtained. Therefore, this research was conducted to determine the pasak bumi distribution and its association within their natural habitat in Batang Lubu Sutam forest. The study was conducted by using the vegetation analysis method using a plotted path determined by purposive sampling. Data analysis was performed by calculating association indices, including the Ochiai index (Oi), Dice index (Di), and Jackard index (Ji). The results showed that pasak bumi were found in the seedling and sapling stage in the research location and form a degree of association with several plants. The species that formed the highest degree of association with the pasak bumi at both levels of regeneration was Shorea leprosula with an Ochiai index value of 0.85 at the seedling level and 0.94 at the sapling level.